Applications of EMbedding and backscattered scanning electron microscopy for morphological and functional assessment of the thymus forcedly removed in children with congenital heart defects during the first weeks of life - A. V. Shabaldin; R. A. Mukhamadiyarov; V. A. Koshelev; A. V. Vedernikova; Yu. I. Rovda; E. O. Grishacheva; I. K. Khalivopulo; N. N. Minyailova; A. A. Lyapin (Медицинская иммунология, 2024)
Thymectomy in a number of clinical situations is an unavoidable step of cardiac surgical treatment of congenital heart defects, but the issue of its effects on development of immunity in early ontogenesis remains open. There is still debates among scientists about the risk of immune deficiency states in children who underwent thymectomy at an early age. One may see completely different opinions, both in domestic and foreign publications. A tool for resolving this issue may be provided by morpho-functional studies of the removed thymic tissue by means of modern scanning electron microscopy techniques. The objective of our study was to assess the possibilities of EMbedding and backscattered scanning electron microscopy for morphological and functional evaluation of the thymus, which was forcedly removed in the infant patients with congenital heart defects over the first weeks of life. The thymus of a newborn infant (postnatal day 27) with congenital heart disease: ventricular septal defect was examined using EMbedding and backscattered scanning electron microscopy imaging after embedding in epoxy resin. The mass of thymus gland was 15.7 g, the dimensions of thymus were: transverse, 3.4 cm; longitudinal, 4.1 cm; thickness, 1.7 cm; volume, 12.4 cm3. The study showed ability of EMbedding and backscattered scanning electron microscopy in morphological and functional assessment of thymus gland considered the central organ of the immune system. Step-bystep visualization from low to high magnifications, from tissues to cells and intracellular structures, as well as layer-by-layer examination of thymic cortex, medulla, interlobular septa and vessels, allows you to effectively assess the functionality of the thymus. This research method is sufficient for scientific research of the forcedly removed thymus since it enables us to visualize its microanatomy, allowing cell phenotyping at different layers of the thymus, studying intercellular interactions of thymocytes with reticulo-epithelial cells, subtle features of Hassall’s bodies and, finally, the process of T lymphocytes’ release from thymus gland.